Optimization of process parameters in friction stir welded dissimilar magnesium alloys using RSM. (2021) - Subramanian, M.; Sathishkumar, N.; Samuel Sasthrigal, Joses; Arunkumar, N.; Hariharan, V.
Abstract: The welding of two dissimilar magnesium alloys is considered as a greatest challenge because of poor metallurgical transition at joints. The FSW process is mostly used for joining different metals which are very difficult to weld through fusion welding technique. In this study the FSW process is used to weld AZ31B and AZ91C magnesium alloys. Three different tool profile (Conical, square and cylindrical type) were used along with three different rotational speeds (900, 1150 and 1400 rpms) and tool traverse speeds (25, 35 and 45 mm/min). The tensile strength was experimentally calculated for all the 15 combinations given by the Box – Behnken model in response surface methodology technique. Three samples in each combination were tested and the average tensile strength was used to find the optimized welding parameters combination in response surface methodology software. The microstructure of the welded region was analysed using scanning electron microscopy to verify the effect of brittle inter – metallic transition at welded joints. The regression equation generated from the Box – Behnken model was used to find the optimized parameters condition. The optimized tensile strength value of 186.721 was obtained from Response Surface Methodology at an optimum parameter combination of a tool rotation speed at 900 rpm with square tool pin head of 45 mm tool traverse speed. The conformal experiment was performed to verify the accuracy of the optimized parameter combination. The conformity test results showed a tensile strength of 182.57 MPa with an error percentage of 2.2% from proposed optimization value which confirms the scope of this study in end functional applications.